Web Browsing: Cognitive-Perceptual Protocols and Body Involvement - Villar, Rafael del (Universidad de Chile. Instituto de la Comunicación e Imagen, 2010)
This paper synthesizes a cognitive-semiotic research on Internet browsing in youth segments of population in Santiago de Chile, about the description of their perceptual, cognitive and corporal protocols. We found six different operating poles in a stratified sample of 540 subjects, differentiated by social class (high, medium, low), age (11-12, puberty; 16-18, ending highschool; 19-24, college or working) and gender.